X=4 is the answer to this
Answer:
Step-by-step explanation:
10
The correct answer is x≈1.01
You're welcome. ;)
Answer:
See below.
Step-by-step explanation:
Here's an example to illustrate the method:
f(x) = 3x^2 - 6x + 10
First divide the first 2 terms by the coefficient of x^2 , which is 3:
= 3(x^2 - 2x) + 10
Now divide the -2 ( in -2x) by 2 and write the x^2 - 2x in the form
(x - b/2)^2 - b/2)^2 (where b = 2) , which will be equal to x^2 - 2x in a different form.
= 3[ (x - 1)^2 - 1^2 ] + 10 (Note: we have to subtract the 1^2 because (x - 1)^2 = x^2 - 2x + 1^2 and we have to make it equal to x^2 - 2x)
= 3 [(x - 1)^2 -1 ] + 10
= 3(x - 1)^2 - 3 + 10
= <u>3(x - 1)^2 + 7 </u><------- Vertex form.
In general form the vertex form of:
ax^2 + bx + c = a [(x - b/2a)^2 - (b/2a)^2] + c .
This is not easy to commit to memory so I suggest the best way to do these conversions is to remember the general method.
The third term of the sequence is 20